Peran Guru PPKn dalam Penguatan Nilai-Nilai Karakter Sebagai Upaya Pencegahan Bullying di SMP Negeri 17 Medan Tahun Pelajaran 2024/2025 (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Bullying is a deviant behavior that can occur among students in the school environment. Bullying behavior will have a negative impact on its victims, both physically and psychologically. The impact on victims can be in the form of psychological disorders, loss of self-confidence, the tendency for students to be difficult to trust others (trust issues), and tend to be alone. Civic Education is present to create (civic disposition/responsibility) the character or attitude of the student's personality and be able to take responsibility. The role of Civics teachers in providing subject matter is very much needed so that students can form character values in behavior, both in the school environment so as to prevent deviations among students such as bullying. Pancasila and Citizenship Education teachers need to educate as well as teach, duly trying to prevent issues of bullying behavior. The objectives of this study are 1) to know the role of Civics Teachers in strengthening character to prevent bullying behavior at SMP Negeri 17 Medan 2) to know the negative impact of bullying behavior among students at SMP Negeri 17 Medan. This type of research is a type of narrative qualitative research. Data collection techniques in this study were interviews, observation and documentation. The sample in this study were all Civics Teachers at SMP Negeri 17 Medan, which were 2 Civics teachers. The results showed that Civics teachers at SMP Negeri 17 Medan have carried out the role of teachers as role models, inspirers, motivators, dynamizers and evaluators. It can be seen that the negative impact of bullying for victims can be in the form of physical and psychological injuries, not wanting to come to school, feeling inferior, losing a sense of security and comfort. Meanwhile, the perpetrators, if not caught or caught bullying, will repeat their actions continuously